Palliative Care for Dialysis-Dependent Pediatric Patients: A Survey of Providers, Nurses, and Caregivers - Joshua Lipsitz; Mark Stockton Beveridge; Katherine Maddox (Kidney360)
Key Points. Providers and nurses recognized the potential added value of palliative care for dialysis-dependent pediatric patients. Most caregivers of dialysis-dependent pediatric patients did not hold positive or negative preconceived notions about a palliative care consultation. Perceived obstacles to palliative care consultation among providers and nurses did not reflect the views of most caregivers. Background. Dialysis-dependent pediatric patients and their families face significant biopsychosocial burdens and low health-related quality of life. Palliative care consultations can alleviate some degree of suffering for patients and families, but remain underutilized within pediatric nephrology. Little is known about how providers, nurses, and caregivers perceive palliative care integration into the multidisciplinary care of dialysis-dependent pediatric patients. Methods. This study surveyed pediatric nephrology providers (physicians and advanced practice providers), inpatient pediatric nephrology bedside nurses, and caregivers of dialysis-dependent pediatric patients at a freestanding tertiary care children's hospital in Dallas, TX. Participants completed a survey regarding knowledge about, experiences with, and perceptions of palliative care in pediatric nephrology. Results. Ten providers, 20 nurses, and 18 caregivers completed the survey. Although 80% of providers and all nurses agreed that palliative care would benefit dialysis-dependent pediatric patients, most believed that palliative care is not as important in pediatric nephrology as it should be. Seventy percent of providers and 45% of nurses believed that they understand the scope of palliative care. Ninety percent of providers and all nurses desired more palliative care education. Of the 22% of caregivers whose child had already received palliative care services, all found the consultation to be helpful. Many providers and nurses worried that a palliative care consultation would signal to families that the nephrology team would be giving up on their child and that their child is approaching the end of life. However, no caregivers thought that a consultation would mean that the nephrology team would be giving up on their child, and only 6% worried that it would indicate that their child is approaching the end of life. Conclusions. These data support further palliative care education for pediatric nephrology providers and nurses and more robust and systematic involvement of subspecialty palliative care for dialysis-dependent pediatric patients.